Hydrological and Flood Analysis of the Cipager River - Fachru, Feisha Arya; Tribhuwana, Awliya; Julfikar, Muklis; Nurdianto, Toto (International Journal of Social Service and Research, 2025)
This study investigates the flood vulnerability of the Cipager River Basin through integrated hydrological and hydraulic analysis. Maximum daily rainfall data from UPTD Mandirancan, UPTD Cilimus, and Cipager Weir were analyzed using four statistical models—Gumbel, Log-Normal, Normal, and Log-Pearson Type III—to estimate design rainfall for return periods of 2 to 100 years. The Log-Normal model produced the most conservative rainfall values, while the Log-Pearson Type III showed anomalous behavior at higher return periods, raising concerns regarding its reliability for modeling extreme hydrological events. Using Manning’s equation, design discharges were derived and compared against the hydraulic capacities of 12 river segments. Results indicate that many segments, particularly Megu Gede, Astana, and Jatimerta, have discharge capacities below 1 m³/s, far below the design discharges associated with longer return periods. This mismatch was further validated during the January 2025 flood, which caused severe inundation in subdistricts such as Weru, Tengahtani, and Gunung Jati. Compounding these risks are physical constraints including channel narrowing, sediment accumulation, and encroachment into riparian zones—conditions exacerbated by weak enforcement of spatial planning regulations. The study recommends structural measures such as river normalization, sediment control, and retention basins, alongside policy enforcement and real-time hydrological monitoring. By aligning statistical discharge modeling with actual river capacity, this research offers a strategic framework for flood risk reduction and supports evidence-based decision-making for climate-resilient watershed management in the Cipager River Basin.